Investigations on pyrolysis of microalgae Diplosphaera sp. MM1 by TG-FTIR and Py-GC/MS: Products and kinetics. (December 2019) - Liu, Cuixia; Duan, Xuejun; Chen, Qishi; Chao, Cong; Lu, Zhenghao; Lai, Qingji; Megharaj, Mallavarapu
Highlights: Behaviors and kinetics of Diplosphaera sp. MM1 were studied by TG-FTIR and Py-GC/MS. Activated energy of Diplosphaera sp. MM1 cultivated in wastewater was lower. Best pyrolytic mechanism function of Diplosphaera sp. MM1 was third-order model. Organic calcium compound decomposition was responsible for secondary weight loss. Abstract: In this work, pyrolysis characteristics and kinetics of microalgae Diplosphaera sp. MM1 cultivated in different mediums were investigated by TG-FTIR and Py-GC/MS. Harvested MM1s biomass varied with the changing in proximate and ultimate analyses presented different weight loss behaviors. The weight loss of MM1s cultivated in dairy and winery wastewater in main pyrolysis region was ~48.4 wt% and ~52.9 wt%, respectively, and both showed secondary weight loss after 570 °C. However, MM1 harvested from BG-11 medium exhibited maximum weight loss of ~63.5 wt% and no secondary weight loss. Further, the activation energies of MM1s harvested from dairy and winery wastewater (176.3 kJ/mol and 130.4 kJ/mol, respectively) were lower than that of BG-11medium (189.4 kJ/mol). The best mechanism function for MM1s pyrolysis was third-order f ( α ) = (1- α ) 3 . Py-GC/MS results of MM1 cultivated in winery wastewater showed highest contents of C4–C10 and C11–C21 that characterized the carbon level of gasoline and diesel, respectively, which are the major components of bio-oils.